Chitosan-Stabilized Selenium Nanoparticles and Metformin Synergistically Rescue Testicular Oxidative Damage and Steroidogenesis-Related Genes Dysregulation in High-Fat Diet/Streptozotocin-Induced Diabetic Rats - Yasmina M. Abd El-Hakim; Amany Abdel-Rahman Mohamed; Safaa I. Khater; Ahmed Hamed Arisha; Mohamed M. M. Metwally; Mohamed A. Nassan; Manal Ewaiss Hassan (MDPI AG, 2020)
Background: this study examined the metformin (MF) and/or chitosan stabilized selenium nanoparticles (CH-SeNPs) efficacy to alleviate the male reproductive function impairment in a high-fat diet feed with low-dose streptozotocin (HFD/STZ) induced type 2 diabetes mellitus (T2DM) diabetic rat model. Methods: control non-diabetic, HFD/STZ diabetic, HFD/STZ+MF, HFD/STZ+CH-SeNPs, and HFD/STZ+MF+CH-SeNPs rat groups were used. After 60 days, semen evaluation, hormonal assay, enzymatic antioxidant, lipid peroxidation, testis histopathology, and the steroidogenesis-related genes mRNA expressions were assessed. Results: in the HFD/STZ diabetic rats, sperm count and motility, male sexual hormones, and testicular antioxidant enzymes were significantly reduced. However, sperm abnormalities and testicular malondialdehyde were significantly incremented. The steroidogenesis-related genes, including steroidogenic acute regulatory protein (StAr), cytochrome11A1 (CYP11A1), cytochrome17A1 (CYP17A1), and hydroxysteroid 17-beta dehydrogenase 3 (HSD17B3), and the mitochondrial biogenesis related genes, including peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGCα) and sirtuin (SIRT), were significantly downregulated in the HFD/STZ diabetic rats. However, CYP19A1mRNA expression was significantly upregulated. In contrast, MF and/or CH-SeNPs oral dosing significantly rescued the T2DM-induced sperm abnormalities, reduced sperm motility, diminished sexual hormones level, testicular oxidative damage, and steroidogenesis-related genes dysregulation. In the MF and CH-SeNP co-treated group, many of the estimated parameters differ considerably from single MF or CH-SeNPs treated groups. Conclusions: the MF and CH-SeNPs combined treatment could efficiently limit the diabetic complications largely than monotherapeutic approach and they could be considered a hopeful treatment option in the T2DM.